Lifestyle Mediates University Students' Consumption Behavior: Financial Literacy and Peer Groups - Silmi Nur Aminah; Ratih Kusumawardhani; Pristin Prima Sari (CV. Sakura Digital Nusantara, 2026)
Purpose – This research examines how financial literacy and peer groups shape university students' consumption behavior, with lifestyle positioned as the mediating variable. The study is motivated by the widespread pattern of consumptive habits among students, a condition driven by limited financial understanding coupled with intense social pressure to keep pace with current trends. Design/methodology/approach – A quantitative design was applied using purposive sampling. Responses were gathered from 100 students enrolled in the 2022 and 2023 cohorts at Universitas Sarjanawiyata Tamansiswa (UST), Yogyakarta. Data were processed through the Partial Least Squares (PLS) technique with the help of SmartPLS software. Finding/Results – The analysis reveals that financial literacy exerts a significant negative effect on students' consumption behavior, whereas peer groups and lifestyle both contribute significant positive effects. Lifestyle is further found to significantly mediate the relationships between financial literacy, peer groups, and students' consumption behavior. Originality/Value – This study's central finding confirms that lifestyle functions as an essential bridge linking internal factors (financial literacy) and external factors (peers) to consumption decisions. Practically, this implies that strengthening financial literacy alongside cultivating a prudent lifestyle is essential for students seeking to curb excessive spending and secure long-term financial stability.